Gastro-oesophageal reflux related cough and its response to laparoscopic fundoplication. Issue 11 (1st November 1998) - Allen, Christopher J; Anvari, Mehran
Abstract : BACKGROUND: This study was designed to determine prospectively the rate of cough before and after laparoscopic Nissen fundoplication performed for the control of gastro-oesophageal reflux disease. METHODS: One hundred and ninety five consecutive patients (76 men) of mean (SD) age 46.9 (14.1) years with proven gastro-oesophageal reflux disease, who were either on long term omeprazole (n = 187) or who had not responded to a trial of omeprazole (n = 8), took part in the study which was carried out in a university teaching hospital that included a regional respiratory referral centre. Patients underwent oesophageal manometry, 24 hour oesophageal pH testing, and symptom score evaluation by an independent observer before and six months after laparoscopic Nissen fundoplication. RESULTS: One hundred and thirty three patients presented with reflux symptoms and 62 with respiratory symptoms; 68% of patients complained of cough before surgery (86% with respiratory symptoms, 60% with gastrointestinal symptoms). The percentage reflux time in 24 hours fell significantly (p<0.0001) from a mean (SD) of 9.38 (10.99)% to 1.22 (2.92)%, lower oesophageal sphincter tone rose significantly (p<0.0001) from a mean (SD) of 7.71 (5.90) mm Hg to 21.74 (10.84) mm Hg, and the cough score fell from a median value of 8.0 (IQR 12.0) to 0 (IQR 3) following surgery. Of the patients with cough, 51% were cough free after surgery and 31% improved. The patients with respiratory symptoms had a higher cough score before (median 12.0 (IQR 5.5) versus 4.0 (IQR 8.75), p<0.0001) and after surgery (median 1 (7.5) versus 0.0 (IQR 1.0), p = 0.0045) than those with gastrointestinal symptoms. CONCLUSIONS: Patients who present to gastroenterologists with severe reflux commonly complain of cough. Laparoscopic Nissen fundoplication is effective in the control of cough in patients with gastro-oesophageal reflux disease, with or without primary respiratory disease.